Isolasi dan Identifikasi Bakteri Toleran Logam Berat dari Sedimen Mangrove di Pengudang dan Tanjung Uban, Pulau Bintan, Indonesia - de Fretes, Charlie Ester; Sutiknowati, Lies Indah; Falahudin, Dede (OLDI (Oseanologi dan Limnologi di Indonesia), 2019)
Isolation and Identification of Heavy Metals Tolerant Bacteria from Mangrove Sediment in Pengudang and Tanjung Uban, Bintan Island, Indonesia. Bacterial searches for remediation of heavy metal pollutants continue to be carried out due to the increasing pollution in the ecosystem as a result of industrialization. This research aims to identification bacteria strains that are tolerant of heavy metals from mangrove sediments in the Pengudang and Tanjung Uban, Bintan Island in 2018. Bacterial isolation was carried out by pour plate method and purified using marine agar (MA) medium. Screening of bacterial isolates was carried out by growing isolates on MA medium with the addition of 100 ppm Pb. In addition, the determination of minimum inhibitory concentration (MIC) was performed on the isolates were tolerant to Pb, Cu, and Cd by addition of heavy metals in 50-1000 ppm concentrations. Identification of heavy metal tolerant isolates was carried out by sequencing the 16S rRNA gene. The results of bacterial isolation from mangrove sediments obtained 48 isolates used for testing the ability of heavy metals tolerant. Screening tests showed that PGD1A, PGD5A, PGD22A, PGD1B, PGD9B, PGD5C, PGD6C, TJU1, TJU5, and TJU7 isolates were heavy metal resistant. The results showed that bacterial isolated from mangrove sediments had MIC values of 800-900 ppm for Pb, 100-800 ppm for Cu and 100-200 ppm for Cd. There are 3 isolates that have high resistance to three kinds of heavy metals such as Bacillus oceanisediminis PGD1A, Vibrio alginolyticus PGD5A, and Halobacillus kuroshimensis PGD9B. This indicates that the isolate can be used efficiently for removal of heavy metals from the ecosystem.